Major depressive disorder and generalized anxiety disorder and response to treatment in hepatitis C patients in Egypt. (August 2015) - Bassiony, MM; Yousef, A; Youssef, U; Salah El-Deen, GM; Abdelghani, M; Al-Gohari, H; Fouad, E; El-Shafaey, MM
Objectives: The aim of the study was to estimate the prevalence and associated correlates of major depressive disorder and generalized anxiety disorder in hepatitis C virus patients before and after treatment and to investigate the relationship between major depressive disorder and generalized anxiety disorder and treatment response. Methods: A total of 116 consecutive hepatitis C virus patients from hepatitis C virus treatment center in Zagazig city, Egypt, were included in the study and divided into treated group ( N = 58) and untreated group ( N = 58). All hepatitis C virus patients were screened for major depressive disorder and generalized anxiety disorder using hospital anxiety and depression scale, and those who screened positive were interviewed to confirm the diagnosis of major depressive disorder and generalized anxiety disorder using DSM-IV-TR diagnostic criteria. These measures were done at baseline and after 12 weeks of treatment or observation. Results: At baseline, 3.5% and 12.1% of hepatitis C virus patients (treated group) had major depressive disorder and generalized anxiety disorder, respectively. After 12 weeks of treatment 37.9% of hepatitis C virus patients (treated group) had major depressive disorder and 46.6% had generalized anxiety disorder. There was a significant statistical difference between hospital anxiety and depression scale scores for depression (3.3 ± 2.3 vs. 6.4 ± 3.2, t = 9.6, p = 0.001) and for anxiety (4.6 ± 2.4 vs. 7.3 ± 3.0, t = 10.2, p = 0.001) before and after treatment. There was also significant statistical difference between treated group and untreated group regarding hospital anxiety and depression scale scores after treatment and observation (depression, treated group 6.4 ± 3.2 vs. untreated group 4.0 ± 2.4, t = 3.7, p = 0.001; anxiety, treated group 7.3 ± 3.0 vs. untreated group 4.5 ± 2.3, t = 4.4, p = 0.001). There was no association between major depressive disorder and generalized anxiety disorder and treatment response. Conclusions: Major depressive disorder and generalized anxiety disorder are common in hepatitis C virus patients after treatment with interferon and ribavirin and were not related to treatment response.